2010
DOI: 10.1017/s1755691011020032
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Newark Supergroup-based astrochronology and geomagnetic polarity time scale (Newark-APTS) for the tempo and mode of the early diversification of the Dinosauria

Abstract: 2010). Implications of the Newark Supergroup-based astrochronology and geomagnetic polarity time scale (Newark-APTS) for the tempo and mode of the early diversication of ABSTRACT: The Newark-APTS established a high-resolution framework for the Late Triassic and Early Jurassic. Palaeomagnetic polarity correlations to marine sections show that stage-level correlations of continental sequences were off by as much as 10 million years. New U-Pb ages show the new correlations and the Newark basin astrochronology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 148 publications
(425 reference statements)
2
88
0
Order By: Relevance
“…At a larger scale, floral data also shows a strong pattern of latitude-related provinciality, with time-transgressive microfloral assemblages being characteristic of low to higher latitudinal sedimentary basin successions (32) resulting from the northward translation of central Pangea, paralleling the pattern observed in larger vertebrates (2). Because the ranges of pollen and spores is often used for long range biostratigraphic correlation, there has been a strong tendency to conflate these biogeographic patterns with a biostratigraphic (i.e., temporal) signal in the absence, or even in the face of, strong, biostratigraphically independent means of temporal correlation (e.g., ref.…”
Section: Discussionmentioning
confidence: 95%
“…At a larger scale, floral data also shows a strong pattern of latitude-related provinciality, with time-transgressive microfloral assemblages being characteristic of low to higher latitudinal sedimentary basin successions (32) resulting from the northward translation of central Pangea, paralleling the pattern observed in larger vertebrates (2). Because the ranges of pollen and spores is often used for long range biostratigraphic correlation, there has been a strong tendency to conflate these biogeographic patterns with a biostratigraphic (i.e., temporal) signal in the absence, or even in the face of, strong, biostratigraphically independent means of temporal correlation (e.g., ref.…”
Section: Discussionmentioning
confidence: 95%
“…Ghost lineages derived from phylogenies indicate that numerous ornithischian lineages must have been present at this time [17], but only three Late Triassic taxa are known from the first 30 Myr of the clade's history (Eocursor, from South Africa; and Pisanosaurus and an unnamed heterodontosaurid from Argentina), each based on incomplete singleton specimens [9, 23,24]. In each case, either the phylogenetic affinities of the taxon or its geological age have been challenged: for example, it has been suggested that one of these specimens (Pisanosaurus) is not an ornithischian at all, whereas Eocursor and the unnamed Argentinean heterodontosaurid have been suggested to be derived from strata of Early Jurassic age [25]. Consequently, ornithischians have been regarded as exceptionally rare faunal components during the Late Triassic and restricted geographically to the middle-high latitudinal regions of southern Pangaea [1][2][3]9].…”
Section: Discussionmentioning
confidence: 99%
“…TS III was deposited under relatively arid climatic conditions and is of Norian and Rhaetian age. Its age is constrained by palaeomagnetic correlation to the Newark basin astrochronology and marine sequences (Kent and Olsen 1999;Muttoni et al 2004;Olsen et al 2011). TS IV conformably overlies TS III and consists of the late Rhaetian top member of the Blomidon Formation and (overlying the North Mountain Basalt) the McCoy Brook Formation, which is of latest Rhaetian to Hettangian (and possibly younger) age.…”
Section: [Traduit Par La Redaction]mentioning
confidence: 99%